2021
DOI: 10.1186/s12889-021-11741-5
|View full text |Cite
|
Sign up to set email alerts
|

Community interventions for improving adult mental health: mapping local policy and practice in England

Abstract: Background Public mental health (PMH) aims to improve wellbeing and prevent poor mental health at the population level. It is a global challenge and a UK priority area for action. Communities play an important role in the provision of PMH interventions. However, the evidence base concerning community-based PMH interventions is limited, meaning it is challenging to compare service provision to need. Without this, the efficient and equitable provision of services is hindered. Here, we sought to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…One review has suggested that some community-based interventions result in a reduction in health inequalities; however, over one-third of studies found no changes between the intervention and control areas (Nickel and von dem Knesebeck, 2020). There is little further research as to whether community-based initiatives work longterm, so the exact effectiveness of this implementation cannot be weighed up (Duncan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One review has suggested that some community-based interventions result in a reduction in health inequalities; however, over one-third of studies found no changes between the intervention and control areas (Nickel and von dem Knesebeck, 2020). There is little further research as to whether community-based initiatives work longterm, so the exact effectiveness of this implementation cannot be weighed up (Duncan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…During the context of the COVID-19 pandemic, different governments worldwide have deployed a variety of policies to reduce infections and deaths from the virus within the workplace [ 32 ]. However, the number of policies that have directly or indirectly aimed to improve workers’ mental health or address mental health needs in the workplace during the pandemic is still limited [ 25 , 30 , 31 , 33 ], and their actual impact on workers has yet to be assessed. Policies that have been implemented to indirectly improve mental health include, for example, increasing the number of resources for the mental health sector; reducing barriers to accessing mental health care during the pandemic context; and training lay staff in basic mental health care and self-care tools [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the WHO definition of health, we define community interventions as "those that involve multi-sector partnerships, emphasise community members as integral to the intervention, and/or deliver services in community settings" (Castillo et al, 2019, p. 35). There are various types of community mental health interventions employed across the UK, but their implementation is quite fragmented and limited (Duncan et al, 2021). Moreover, they generally focus on individual risk factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…, 2019, p. 35). There are various types of community mental health interventions employed across the UK, but their implementation is quite fragmented and limited (Duncan et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation